Policy issues in genetically modified crops : a global perspective - Singh, Pardeep; Borthakur, Anwesha; Singh, Aditya Abha; Kumar, Ajay, PhD; Singh, Kshitij K. (Academic Press, 2021)
Policy Issues in Genetically Modified Crops: A Global Perspective contains both theoretical and empirical evidence of a broad range of aspects of GM crop policies throughout the world. Emphasizing world agriculture production and ethics of GM crops, the book balances insights into the various discussions around the use of GM crops including soil health, effects on animals, environmental sustainability impact, and ethical issues. The book presents aspects of GM crop policies and prevailing controversies throughout the world, in 5 sections containing 23 chapters. Beginning with the discussion of the policies related to GM crops, the book dives deep into issues related to food insecurity, agricultural sustainability, food safety, and environmental risks. Section 5 also captures the recent advances in agricultural biotechnology encompassing research trends, the nano-biotech approach to plant genetic engineering, and other transformation techniques in crop development. The contributors of the book represent different backgrounds, providing a holistic overview of diverse approaches and perspectives. Policy Issues in Genetically Modified Crops: A Global Perspective is a valuable resource for researchers in agricultural policy and economics, agricultural biotechnology, soil science, genetic engineering, ethics, environmental management, sustainable development, and NGOs. Discusses ethics, varieties, research trends, success, and challenges of genetic modification Addresses both crop production and potential health impacts Includes extensive theoretical research and studies